The Integrated Augmented Reality and Google Scholar as the Test Instrument to Improve High Order Thinking Skills and Digital Literacy Skills - Dzulfiqar Satria Waliyuddin; Dwi Sulisworo (Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Jember, 2021)
Abstract Evaluation instruments in the student learning process in interactive, fun, challenging, motivating, and developing students 'creativity and independence are needed to improve students' High Order Thinking Skills (HOTS) and digital literacy skills (DLS). HOTS and digital literacy are part of the 21st-century skills that are important for every individual. This study developed a test instrument integrated with Augmented Reality (AR) and Google Scholar (GS) to encourage HOTS and students' digital literacy skills. This type of research was development research. The subject matter was the scale and comparison. Product trials were applied to 11th-grade students in Sleman, Indonesia. Product validity was based on expert judgment, item validity, distinguishing power, difficulty level and reliability. AR was created using the ARLOOPA application operated with android. The research instrument was designed to increase HOTS and DLS.